OPTIMIZATION DESIGN OF GANTRY CRANE SKIN STRUCTURE SYSTEM BASED ON RELIABILITY ANALYSIS - HAN Wei; YU LanFeng; WANG PingPing; YAN Fei (Jixie qiangdu)
Put forward a kind of skin structure crane optimization design method based on reliability analysis. Considering the randomness of size parameters,material properties and wind load in the skin structure crane design,using Monte-Carlo method of Latin hypercube sampling（ LHS） technique to calculate the reliability of structure system. Through probabilistic sensitivity analysis to determine the optimal design variables,with the total quality of metal structural system of skin structure crane as the goal,to optimize the design by using the finite element analysis software ANSYS,relative to the initial design the quality of skin structure is reduced by 23. 8%,the overall reliability is used effectively,avoids the local reliability surplus,saves manufacturing cost.